PHARMACOEPIDEMIOLOGY OF PHYSICIANS' INDICATIONS IN PATIENTS WITH POSTINFARCTIONCARDIOSCLEROSIS - O. N. Kurochkinа; A. L. Khokhlov; N. M. Boyankova (IRBIS LLC, 2015)
Pharmacoepidemiologic study evaluating physicians' indications in patients with history of myocardium infarction at hospital discharge indications as well as in outpatient treatment recommendations. The results were compared to previous IHD pharmacoepidemiology data of Russian Federation. It was shown that majority of patients with history of MI have received therapy referred to disease prognosis improvement.